STRATEGI PEMASARAN PRODUK DEPOSIT DI BAITUL MAAL WA TAMWIL AL-FATAYA PAYAKUMBUH - Nadya Utami; Zuwardi (ADISAM PUBLISHER, 2023)
The background of this research is the lack of knowledge in the community about i-Deposit products, so that there are many methods that are used by each bank in carrying out the strategy. One of them is by promoting it at least by providing explanations or knowledge to the community about the idea deposit product i. This research aims to find out how the marketing strategy for the deposit product is in the face of competition between other Islamic financial institutions. In this description, the research used is in the form of field research which is qualitatively descriptive in nature by using iSWOT analysis. Because of that, the writer must know how the condition of the company, namely the internal and external factors that influence the marketing strategy that exists in the company, i. The Weakness-Opportunities (WO) strategy gets a weight of 3.42. While the Strength-Threats (ST) strategy gets a weight of 2.95. The Weakness-Threats (WT) strategy gets a weight of 2.27. So that from the results of calculating the weight of the SWOT Matrix score, BMT Al-Fataya can use and make the most of its strengths and opportunities so as to achieve increased marketing of deposit products. Then BMT Al-Fataya is able to face weaknesses and threats in marketing these deposit products.